2022
DOI: 10.1186/s44147-022-00113-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electrokinetic-enhanced oil recovery (EK-EOR): a systematic review

Abstract: Hydrocarbons continue to play an important role in providing affordable energy to meet rising energy demand. Amidst growing concerns on the environmental impact of oil and gas production processes, many researchers are increasingly exploring environmentally sustainable methods of extracting hydrocarbons from the reservoir. The introduction of direct current into the pore space activates mechanisms that enhance fluid flow, reduces produced water, decreases associated hydrogen sulfide production, and leaves no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Statements about the need for special economic mechanisms for the implementation of EOR technologies have become commonplace. However, specific and effective solutions have not been developed or adopted in almost any country in the world today, perhaps with the exception of China [176].…”
Section: World Experience In Using Mip and Eormentioning
confidence: 99%
“…Statements about the need for special economic mechanisms for the implementation of EOR technologies have become commonplace. However, specific and effective solutions have not been developed or adopted in almost any country in the world today, perhaps with the exception of China [176].…”
Section: World Experience In Using Mip and Eormentioning
confidence: 99%
“…However, petroleum reservoirs are sediments derived from originally existing rocks with aggregarde of minerals that have ionisable surface group when in contact with aqueous phase due to hydrolysis reactions [29]. Consequently, the formation of the lelectric double layer within hydrocarbon reservoirss is possible via dissociation reactions surface ionsable groups of minerals and the pH, zeta potential, free energy, and its thickness affects wettability [30] and capillary imbibition within the TZ.…”
Section: Introductionmentioning
confidence: 99%
“…This is to facilitate increase in the recovery rate (RR) of hydrocarbon and also to determine the extent to which nanoparticles can influence the ability of the injected fluid(s) to easily displace hydrocarbon for possible exploration. The work of (Ikpeka et al, 2022) based on electro-kinetic EOR done by introducing direct current into the reservoir rocks crevices revealed that electro-kinetic EOR assists in activating the recovery process and stated that a major setback to this method is the deposition of cathodic salt and gas generation but on the average, EOR can be electrically triggered to facilitate production of more volume of hydrocarbon. (Yin and Zhou, 2021) established that oil recovery can be enhanced in fractured reservoirs of low permeability.…”
Section: Introductionmentioning
confidence: 99%